2001
DOI: 10.1093/humupd/7.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Impact of genetic engineering on the understanding of spermatogenesis

Abstract: To date, about 100 genes have been found, by genetic engineering, to be implicated in spermatogenesis. Primordial germ cells, spermatogonia, spermatocytes I and elongating spermatids are particularly sensitive. Transgenic and knockout mice permit an approach to be made to the question of genetic factors involved in DNA damage repair, thermal injury, sperm chromatin compaction and sex-specific recombination. Knockout mice reveal unexpected functional redundancies of testis-specific genes. This review considers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
71
0
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 216 publications
0
71
0
5
Order By: Relevance
“…We are currently investigating the potential binding partner(s) of CIB1 in order to further determine the mechanism by which CIB1 regulates spermatogenesis. Our findings here suggest that CIB1 null mice may provide a useful research model for understanding human male idiopathic infertility and thus fertility drug targets (4,6).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We are currently investigating the potential binding partner(s) of CIB1 in order to further determine the mechanism by which CIB1 regulates spermatogenesis. Our findings here suggest that CIB1 null mice may provide a useful research model for understanding human male idiopathic infertility and thus fertility drug targets (4,6).…”
Section: Discussionmentioning
confidence: 71%
“…Spermatogenesis is the long, complex process by which germ cells are produced through successive periods of regulated cell proliferation, meiosis, and haploid differentiation (6,19). During spermatogenesis in the mammalian testis, stem cells proliferate to produce spermatogonia, which differentiate into primary spermatocytes.…”
mentioning
confidence: 99%
“…Nonetheless, our successful production of offspring from an infertile male mouse suggests a promising possibility for the gene therapy approach in the treatment of male infertility. A number of infertile mutants in mice are caused by genetic defects in Sertoli cell function, which strongly suggest that some cases of human male infertility may be associated with Sertoli cell dysfunction (49), and improvements in the gene transfer technology will certainly increase mature spermatozoa production. Extensive studies on sequencing spermatogenesis genes and their site of expression as well as how to safely correct genes are clearly required for the possibility of gene therapy for male infertility at this stage of research.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse studies have shown that 4100 genes are involved in spermatogenesis. 3 When knockout mice for these genes were made, defects were often pleiotropic and thus not restricted to an impaired spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%